Development of a springback prediction for a hybrid laminate with sensor functionality. Issue 1 (June 2021) - Graf, A.; Kräusel, V.; Rodio, A.; Lanzotti, A.
Abstract: Developing the idea of lightweight construction even further, we have considered the integration of additional functionalities directly into the semi-finished product. Enormous weight savings can be achieved through integration into a large-scale production process. However, these new material composites in the form of hybrid laminates are accompanied by new challenges in terms of forming properties. In particular, there is a need to investigate how the plastic layer with sensor functionality in a hybrid laminate impacts its springback properties. To this end we designed tests using the design of experiments (DOE) technique and identified the significant factors using analyses of variance (ANOVA). Due to the material combination we had to include additional factors such as temperature and punch holding time. Our research showed an adequate distinction between springback and spring-forward behaviour. Utilising FEM, the results were simulated and compared. Our biggest challenge lay in the exact description of the interface between metal and plastic in the FEM.